Slow magnetization dynamics in Co(ii)/Co(iii) triethanolamine/pivalate complexes - Sarto, Carolina; Rouzières, Mathieu; Liu, Jun-Liang; Bamberger, Heiko; van Slageren, Joris; Clérac, Rodolphe; Alborés, Pablo (Dalton transactions : an international journal of inorganic chemistry, 2018)
We report the synthesis, structural characterization and a combined computational and experimental study of the magnetic properties of two pivalate cobalt complexes, a mononuclear Co(ii) one and a tetranuclear Co(ii) Co(iii) mixed valence polynuclear one. The latter shows SMM behaviour revealed under an applied DC field with a thermal barrier of ca. 30 cm competing with direct and Raman relaxation processes. The Orbach thermal barrier can be understood from the doublets energy ladder arising from the anisotropic exchange interaction among ground S = 1/2 of each Co(ii) sites. The strong local zero-field splitting of the S = 3/2 Co(ii) states affords these well isolated ground Kramers doublets. DC and AC magnetic susceptibility measurements as well as HF-EPR spectra support this interpretation. CASSCF quantum chemical computations have been also performed in order to aid the overall comprehension of the magnetic behaviour in the reported complexes.